Competition of XA and L21B ordering in Heusler alloys Mn2CoZ (Z = Al, Ga, Si, Ge and Sb) and its influence on electronic structure. (January 2017) - Xin, Yuepeng; Hao, Hongyue; Ma, Yuexing; Luo, Hongzhi; Meng, Fanbin; Liu, Heyan; Liu, Enke; Wu, Guangheng
Abstract: Competition between the highly-ordered XA structure and disordered L21 B structure in Heusler alloys Mn2 CoZ (Z = Al, Ga, Si, Ge, Sb) has been investigated. The relative stability of the two structures strongly depends on the main group element Z. When Z belongs to Al or Ga, the XA structure is stabler, but when Z belongs to Si, Ge or Sb, the L21 B structure gains stability and is lower in energy. This is related to the different number of valence electrons in main group element Z, which influences the DOS structure near the Fermi level and changes N(EF ). The energy difference ΔE between the XA and L21 B structures may be used to estimate the tendency to form L21 B structure in different Heusler alloys qualitatively. A large negative ΔE is preferable to retard the A-C site disorder and retain the highly-ordered XA structure. That is just the case in Mn2 CoAl. A robust half-metallicity is observed in Mn2 CoSi, Mn2 CoGe and Mn2 CoSb, they are always half-metallic under either XA or L21 B structure. But in Mn2 CoAl and Mn2 CoGa, their spin gapless semiconducting character will be destroyed and replaced by a half-metallic state if L21 B disorder occurs. Finally, these results suggest that the L21 B structure should be considered together with XA structure when discussing the electronic structure of "inverse" Heusler alloys. Highlights: L21 B structure is energetically favored in some Mn2 -based Heusler alloys. L21 B ordering should be considered together with XA in inverse Heusler alloys. Half-metallicity is robust in Mn2 CoZ (Z = Si, Ge, Sb). Large negative ΔE between XA and L21 B helps to retain SGS character in Mn2 CoAl.